Political stability, regulation and investment in the African mobile markets - Goodiel Moshi; Hitoshi Mitomo (International Telecommunications Society (ITS), 2014)
This study attempted to analyze the effect of regulation and political stability in allocation of mobile telecommunication investments in the African continent between year 2001 and 2011. In order to better understand the dynamics of investment in telecommunications, a framework was developed to understand the factors that determine investments in telecom industry at country and industry level, particularly: institutions, market size/demand level, market structure and investing cost. The results show that investments in the telecommunications industry are positively dependent on liberalization that opened the market to private sector; however, no statistical evidence was found on the effect of political stability measured by the democratic process. Further, the study has shown that market structure especially competition, and market size and cost of investing in a country are important factors for investments allocation in mobile telecommunications industry among African countries.
Keywords: L51; L1; C23; C26; D43; 330; mobile telecommunication; investment; political stability; liberalization; African countries